An application of univariate and multivariate approaches in fMRI to quantifying the hemispheric lateralization of acoustic and linguistic processes - McGettigan, Carolyn (2011)
The question of hemispheric lateralization of neural processes is one that is pertinent to a range of subdisciplines of cognitive neuroscience. Language is often assumed to be left lateralized in the human brain, but there has been a long running debate about the underlying reasons for this. We addressed this problem with fMRI by identifying the neural responses to amplitude and spectral modulations in speech, and how these interact with speech intelligibility, to test previous claims for hemispheric asymmetries in acoustic and linguistic processes in speech perception. We used both univariate and multivariate analyses of the data, which enabled us to both identify the networks involved in processing these acoustic and linguistic factors, and to test the significance of any apparent hemispheric asymmetries. We demonstrate bilateral activation of superior temporal cortex in response to speech-derived acoustic modulations in the absence of intelligibility. However, in a contrast of amplitude- and spectrally-modulated conditions that differed only in their intelligibility (where one was partially intelligible and the other unintelligible), we show a left-dominant pattern of activation in insula, inferior frontal cortex and superior temporal sulcus. Crucially, multivariate pattern analysis (MVPA) showed that there were significant differences between the left and the right hemispheres only in the processing of intelligible speech. This result shows that the left hemisphere dominance in linguistic processing does not arise due to low-level, speech-derived acoustic factors, and that MVPA provides a method for unbiased testing of hemispheric asymmetries in processing.